Gender Analysis of the Success Rate of Integrated Crop Management Field School Program - Muthiah, Falah; Hubeis, Aida Vitayala (Departemen Sains Komunikasi dan Pengembangan Masyarakat, Fakultas Ekologi Manusia, IPB, 2017)
Gender inequalities in development programs is problem that still going on. One of program from the government that relate to agricultural development policies and apply the principle of gender mainstreaming is Integrated Crop Management Field School Program (SL-PTT) in rural areas. The general purpose of this research is to analyze the level of gender equality in SL-PTT program, and analyze the relationship between the level of gender equality with success rate of SL-PTT program. This research using quantitative data with survey method using simple random sampling technique and analyzed by cross tabulation and Rank Spearman. This research supported by qualitative data with in-depth interviews. The results showed that there is a positive and significant correlation between the level of gender equality Â and success rate of SL-PTT program.Keywords: gender analysis, gender equality, the success rate of the program================================================ABSTRAKProgram pembangunan yang belum memenuhi adanya kesetaraan gender menjadi permasalahan yang sampai saat ini berlangsung. Salah satu program dari pemerintah yang berkaitan dengan kebijakan pembangunan pertanian yang menerapkan prinsip pengarusutamaan gender adalah program Sekolah Lapang Pengelolaan Tanaman terpadu (SL-PTT) di perdesaan. Tujuan umum penelitian ini adalah untuk menganalisis tingkat kesetaraan gender program SL-PTT, dan menganalisis hubungan antara tingkat kesetaraan gender dengan tingkat keberhasilan program SL-PTT. Penelitian ini menggunakan data kuantitatif dengan metode survei dengan menggunakan teknik simple random sampling dianalisis menggunakan tabulasi silang dan Rank Spearman didukung dengan data kualitatif dengan wawancara mendalam. Hasil penelitian menunjukan bahwa terdapat hubungan positif dan signifikan antara tingkat keterlibatan peserta SL-PTTÂ dengan tingkat keberhasilan program SL-PTT.Kata Kunci : Â Analisis gender, kesetaran gender, keberhasilan program